Effect of Temperature On The Dissociation Of Cysteine In Aqueous Solutions From Conductivity Measurements - AI-Taiar, A.H.; Bhaya, N.D.; Ridha, S.H.; AIÂ Sammarrie, H.B.; AI-Fakhry, K.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The  conductance  of  solu ti ons  of  cysteine  in  water  at  different concentrations and temperatures has been measured. These solutions obey Onsagcr  equation  and  give  linear  relations  especially  at  low concentrations. In more concentrated solutions a deviation from the equation is observed.The molar conductivity of these solutions decreases with t he increase  in concen trations at constant temperature.The  values of  the ionization constants and the conductivity at  infin itedilution for each temperature have been calcu lated.